Konteks Situasi dan Konteks Budaya yang Ditemukan dalam “Sonnet XVIII” William Shakespeare - Della Rizky Ananda; Ridwan Syahputra; Ulpah Maisari; Atma Jonar Asih; Juniar (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
This final project uses the grammar of the halliday functional because sequentially this text is studied in terms of the language the text functions, and the way the function relates to the context; which includes the context of the situation and the cultural context. This final project aims to present the context of the situation and the cultural context contained in the sonnet. This final project aims to describe the metafunction meaning contained in the sonnet, to describe the context of the situation reflected in the metafunction analysis, and finally to describe the cultural context. Data sources include words, phrases, sentences, and events in the sonnet. the following is the data collected. Read the text carefully and repeatedly, identify data related to the topic, classify the data into two groups, namely the meaning of metafunction, and the context of the situation and cultural context. The data were analyzed by determining the ideational, interpersonal and textual meanings, then this context as classified in the previous steps. Based on the analysis that has been studied, the context of the situation contained in the metafunction analysis shows: the field is a love poem with social activities that tells about a friend; the tenor is a connoisseur of love, a fan of its light, and on a metaphorical level, man to God; The mode is not a verbal-visual channel, it is text written to be said aloud with one-sided dialogue and an invisible recipient. In this cultural context, the aim is to express admiration, the structure begins with comparison, explanation and contradiction in the middle, and ends with affirmation, and the structure of the sonnet has linguistic characteristics indicating that the genre of this text is literary; poetry in sonnet form.